The Human Cytomegalovirus Ribonucleotide Reductase Homolog UL45 Is Dispensable for Growth in Endothelial Cells, as Determined by a BAC-Cloned Clinical Isolate of Human Cytomegalovirus with Preserved Wild-Type Characteristics - Hahn, Gabriele (American Society for Microbiology, 2002)
An endothelial cell-tropic and leukotropic human cytomegalovirus (HCMV) clinical isolate was cloned as a fusion-inducing factor X-bacterial artificial chromosome in Escherichia coli, and the ribonucleotide reductase homolog UL45 was deleted. Reconstituted virus RVFIX and RVΔUL45 grew equally well in human fibroblasts and human endothelial cells. Thus, UL45 is dispensable for growth of HCMV in both cell types.